Review of Polymer-Based Composites for Electromagnetic Shielding Application - Yuqi Wang; Wei Zhao; Linli Tan; Yingru Li; Liu Qin; Shidong Li (Molecules, 2023)
The rapid advancement of electronic communication technology has greatly aided human productivity and quality of life, but it has also resulted in significant electromagnetic pollution issues. Traditional metals and alloys are often used for electromagnetic interference (EMI) shielding due to their excellent electrical conductivity. However, they have drawbacks such as being heavy, expensive, and having low corrosion resistance, which limits their application in electromagnetic shielding. Therefore, it is crucial to develop novel EMI shielding materials. Polymers, being highly flexible, corrosion-resistant, and possessing high specific strength, are frequently employed in electromagnetic shielding materials. In this review, we firstly introduce the basic theory of electromagnetic shielding. Then, we outline the processing methods and recent developments of polymer-based electromagnetic shielding composites, including uniform-, foam-, layered-, and segregated structures. Lastly, we present the challenges and prospects for the field, aiming to provide direction and inspiration for the study of polymer-based electromagnetic shielding composite materials.